Topical ganciclovir in the treatment of acute herpetic keratitis - Khalid F Tabbara (Dove Medical Press, 2010)
Khalid F Tabbara1,2,3, Noorjehan Al Balushi11The Eye Center and The Eye Foundation for Research in Ophthalmology, Riyadh, 2Department of Ophthalmology, College of Medicine, King Saud University, Riyadh, Kingdom of Saudi Arabia; 3The Wilmer Ophthalmological Institute of The Johns Hopkins University School of Medicine, Baltimore, Maryland, USAAbstract: Herpetic keratitis is caused by herpes simplex virus (HSV) and is a common cause of corneal blindness. Following a primary ocular herpetic infection, latency of the virus occurs, followed by subsequent recurrences of herpetic keratitis. Such recurrences may lead to structural damage of the cornea. Recurrent herpetic keratitis is a common indication for corneal transplantation. Recurrences of herpetic keratitis in the corneal graft may lead to corneal graft rejection. Several antiviral agents for HSV are available, including the thymidine analogs. Prolonged use of thymidine analogs may lead to toxicity of the ocular surface, including epithelial keratitis, corneal ulcers, follicular conjunctivitis, and punctal occlusions. Availability of topical antiviral agents that are safe and effective in the treatment and prophylaxis of herpetic keratitis is highly desirable. Ganciclovir is a potent inhibitor of members of the herpes virus family. The drug has been used systemically for the treatment of cytomegalovirus (CMV) retinitis. Its hematologic toxicity secondary to systemic administration led to its limited use in herpetic infections. On the other hand, topical ganciclovir has been shown to be as safe and effective as acyclovir in the treatment of herpetic epithelial keratitis. Furthermore, topical ganciclovir can reach therapeutic levels in the cornea and aqueous humor following topical application. Several clinical trials have shown that topical ganciclovir 0.15% ophthalmic gel is safe and effective in the treatment and prophylaxis of herpetic epithelial disease. Long-term use of ganciclovir ophthalmic gel in patients with penetrating keratoplasty following herpetic keratitis has prevented recurrences of the disease. Topical ganciclovir ophthalmic gel is well tolerated, does not cause toxic effects on the ocular surface, and does not cause hematologic abnormalities. Clinical studies have underscored the potential role of ganciclovir ophthalmic gel in the treatment and prophylaxis of herpetic epithelial keratitis. Future randomized, controlled, multicenter, prospective clinical trials are needed to assess the long-term safety and efficacy of topical ganciclovir in the treatment and prevention of herpetic keratitis and uveitis.Keywords: herpetic keratitis, cornea, herpes simplex, ganciclovir, acyclovir